Daily living and rehabilitation needs in patients and caregivers affected by myeloproliferative neoplasms (MPN): A qualitative study. Issue 7 (6th July 2021) - Rossau, Henriette Knold; Kjerholt, Mette; Brochmann, Nana; Tang, Lars Hermann; Dieperink, Karin Brochstedt
Abstract: Aims and Objectives: To explore experiences of daily living and identify rehabilitation needs in patients and caregivers living with myeloproliferative neoplasms. Background: Myeloproliferative neoplasms are chronic haematological cancers. Studies report a high symptom burden but little is known about supportive care and rehabilitation for this patient group. Design: Qualitative study with a phenomenological approach using focus group interviews to gather knowledge about the participants' lived experiences. Methods: Forty‐eight patients and seven caregivers attending a 5‐day rehabilitation course were interviewed in 12 focus groups. Systematic Text Condensation was used to analyse the interviews. Reporting adhered to COREQ. Results: Two main themes for patients were found: The loss of choice and identity due to the need to prioritise energy and The schism of being a person but also a patient . Patients described how living with myeloproliferative neoplasms meant having to prioritise energy and, therefore, losing freedom to choose activities. This changed their identity and impaired their quality of life. Patients of working age seemed to struggle the most in balancing the disease, family, social relationships and work. One main theme was found for caregivers: Influence of the disease . Caregivers reported how the disease limited their social lives, that the disease brought psychological strain, extra work, and that communication between couples was impaired. When both patients and caregivers participated in rehabilitation courses, they reported better understanding between couples and more open conversations. Rehabilitation needs identified were mainly in relation to psychosocial support and patient education, although needs varied across patients and caregivers. Conclusions: Patients and caregivers expressed difficulties in adjusting to the lives the disease enforced upon them. Our findings indicate that myeloproliferative neoplasms patients and their caregivers would benefit from a combined model of psychosocial support, patient education, peer support and rehabilitation interventions based on an individual needs assessment. Relevance to clinical practice: Nurses can be responsible for individual needs assessments and refer patients and caregivers to suitable supportive care and rehabilitation interventions. Trial registration details: The study was approved by the Danish Data Protection agency (J.nr. 2008‐58‐0035).